(untitled) (International Journal of Environmental Sciences, 2025)
Nano-sized Co-doped MgFe₂O₄ was effectively synthesized via a cost-effective co-precipitation method. Systematic characterization was carried out by using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), and Fourier-transform infrared spectroscopy (FTIR). The XRD and FTIR results confirmed the evaluation of a spinel structure in the synthesized material. XPS investigation verified the presence of Co 2p, Fe 2p, Mg 2p, and O 1s elements in the nanoparticles, indicating successful cobalt incorporation. Electrochemical impedance spectroscopy revealed that the capacitance behavior of the Co-doped MgFe₂O₄ electrodes improved with increasing temperature. Furthermore, cyclic voltammetry (CV) analysis demonstrated the highest specific capacitance at a scan rate of 2 mV/s. These findings suggest that the synthesized Co-doped MgFe₂O₄ nanoparticles exhibit promising electrochemical properties, suitable for supercapacitor applications.